The agronomic mechanism of root lodging resistance and yield stability for sweet corn in response to planting density and nitrogen rates at different planting dates - Liang, Qinggan; Chang, Hailong; Chen, Hongrong; Wu, Qingdan; Qin, Yuanxia; Wang, Zhuqing; Wang, Gang; Li, Xuhui; Chen, Weiwei; Wu, Jiantao; Wang, Qinnan; Wang, Jianqiang (Frontiers in Plant Science, 2025)
A three-cycle field experiment was conducted to investigate the underlying agronomic mechanism on modulating the root lodging resistance and yield stability of sweet corn in response to the planting density and nitrogen rate during different growth seasons. The experiment comprised two factors with six treatments and was conducted in a split-plot design. Two nitrogen (N) rates (200 kg ha-1, N200; 150 kg ha-1,N150) applied to the main plots and three planting densities (20 cm plant space, D20; 25 cm plant space, D25; and 30 cm plant space, D30; 60 cm rows space for all plots) as subplots. The results indicated that the plants in N150D25 presented better root system architecture, greater root biomass, and more roots per plant. These effects are mediated by the underlying metabolism of endogenous phytohormones, which balance the absorbing and anchoring function of the root system. This further improved the development of plant crown architecture, including stem nodes and ear leaf traits, and further coordinated dry matter dynamics and lignin metabolism between the root and shoot organs. These observations may account for the resistance of the roots to lodging in this treatment. The maximum yield output was achieved in the plants under N150D25 via a significant increase in individual ear fresh weight, kernel number per row, and grain number per ear via path analysis. Compared with that of N200D30 (local field management), the yield of N150D25 plants increased by 22.33%–30.00% during the three growing seasons. Notably, the yield stability was achieved by significantly reducing the coefficient of variation (CV) of cob length and diameter, ear diameter, kernel row number per plant and grain number per plant. Among these factors, the planting date had a considerable effect on ear fresh weight, cob fresh weight, ear length, cob diameter, cob length and kernel row number by significantly increasing the degree of variation. This finding indicated that the planting date is a crucial factor that should be accounted in field crop management. Our findings provide a scientific basis for high-yield production of sweet corn in tropical regions during the “off season” period.